Decision-Making and Problem-Solving System at JHS IT Darul Hikmah, West Pasaman Regency - Rahmawati, Milatul; Hadiyanto, Hadiyanto; Irsyad, Irsyad; Gistituati, Nurhizrah (International Journal of Educational Dynamics, 2024)
Decision-making plays a crucial role in the management of educational institutions, as decisions made by the principal must be implemented by subordinates and other individuals associated with the institution. The effectiveness of decision-making directly impacts an organization's success, while mistakes can lead to significant consequences, such as loss of reputation or financial resources. This study investigates the problem-solving and decision-making system at JHS IT Darul Hikmah. The objective is to understand how the principal applies this system to achieve the school's goals and address challenges effectively. This study adopts a qualitative approach, utilizing descriptive study methods to analyze the decision-making processes at JHS IT Darul Hikmah. The findings reveal that decision-making involves deliberation with teachers to ensure democratic practices and alignment with the school’s vision and mission. However, the study also identifies several factors that hinder effective decision-making, including limited teacher participation in deliberations and financial constraints. These challenges highlight the need for more comprehensive strategies to improve decision-making at JHS IT Darul Hikmah.